THE RELATIONSHIP OF FACTORS IN IMPLEMENTATION OF THE POLICY TO THE SUCCESS OF THAI WOMWN EMPLOYMENT FUND IN THE CATEGORY OF WORKING CAPITAL OF THE DISTRICT COMMUNITY DEVELOPMENT OFFICE IN SAKON NAKHON PROVINCE’S - Sridacha, Aonratchada; Yongvanit, Sekson; Sansri, Rakpong (Journal of Humanities and Social Sciences Mahamakut Buddhist University Isan Campus, 2024)
This research aims to (1) study the level of factors in the implementation of the revolving fund women’s development fund policy of the Sakon Nakhon Province Community Development Office and (2) study the relationship between the factors in the implementation of the policy that affect the success of the revolving fund women’s development fund of the district community development offices in Sakon Nakhon Province. The research instrument was a questionnaire. The sample consisted of 260 female members with outstanding debts using the Taro Yamane formula. The data collected from the questionnaires were analyzed using SPSS for Windows. Descriptive statistics were used, including means, and inferential statistics, which are statistics used to analyze data at a 2-variable level. The relationship of each sub-characteristic of the independent variable with the dependent variable was analyzed by finding the Peason’s product moment correlation coefficient. The research results found that (1) the level of factors in the implementation of the revolving fund women’s development fund policy of the Sakon Nakhon Province Community Development Office, the overall policy implementation factor was at the highest level (= 4.24) and the spatial limitation factor Overall, it is at a high level (= 4.19) and (2) the relationship of factors in policy implementation that affect the success of the Women’s Development Fund in the revolving fund type of Community Development Office in Sakon Nakhon Province has a moderate relationship level with statistical significance at the 0.01 level. Recommendations from the research should have a policy to support public relations, should support participation according to the roles and responsibilities of stakeholders and should develop a monitoring system before, during and after project approval to make policy implementation clearer.